Fatal infantile mitochondrial encephalomyopathy, hypertrophic cardiomyopathy and optic atrophy associated with a homozygous OPA1 mutation. Issue 2 (11th November 2015) - Spiegel, Ronen; Saada, Ann; Flannery, Padraig J; Burté, Florence; Soiferman, Devorah; Khayat, Morad; Eisner, Verónica; Vladovski, Eugene; Taylor, Robert W; Bindoff, Laurence A; Shaag, Avraham; Mandel, Hanna; et al.
Abstract : Background: Infantile-onset encephalopathy and hypertrophic cardiomyopathy caused by mitochondrial oxidative phosphorylation defects are genetically heterogeneous with defects involving both the mitochondrial and nuclear genomes. Objective: To identify the causative genetic defect in two sisters presenting with lethal infantile encephalopathy, hypertrophic cardiomyopathy and optic atrophy. Methods: We describe a comprehensive clinical, biochemical and molecular genetic investigation of two affected siblings from a consanguineous family. Molecular genetic analysis was done by a combined approach involving genome-wide autozygosity mapping and next-generation exome sequencing. Biochemical analysis was done by enzymatic analysis and Western blot. Evidence for mitochondrial DNA (mtDNA) instability was investigated using long-range and real-time PCR assays. Mitochondrial cristae morphology was assessed with transmission electron microscopy. Results: Both affected sisters presented with a similar cluster of neurodevelopmental deficits marked by failure to thrive, generalised neuromuscular weakness and optic atrophy. The disease progression was ultimately fatal with severe encephalopathy and hypertrophic cardiomyopathy. Mitochondrial respiratory chain complex activities were globally decreased in skeletal muscle biopsies. They were found to be homozygous for a novel c.1601T>G (p.Leu534Arg) mutation in the OPA1 gene, which resulted in a marked loss of steady-state levels of the native OPA1 protein. We observed severe mtDNA depletion in DNA extracted from the patients' muscle biopsies. Mitochondrial morphology was consistent with abnormal mitochondrial membrane fusion. Conclusions: We have established, for the first time, a causal link between a pathogenic homozygous OPA1 mutation and human disease. The fatal multisystemic manifestations observed further extend the complex phenotype associated with pathogenic OPA1 mutations, in particular the previously unreported association with hypertrophic cardiomyopathy. Our findings further emphasise the vital role played by OPA1 in mitochondrial biogenesis and mtDNA maintenance.